2017
DOI: 10.1186/s13027-017-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes associated with cervical precancerous lesions and cancer in the highest area of cervical cancer mortality, Longnan, China

Abstract: BackgroundThe mortality of cervical cancer in Longnan is as high as 39/10 million, ranking first in China.MethodsBetween 2012 to 2016, 329 samples with cervicitis, cervical intraepithelial neoplasia grade 1 to 3 (CINI to III), and invasive squamous cell carcinoma (SCC) were collected. HPV genotypes were examined with a validated kit for 23 different HPV subtypes.ResultsCompared to cervicitis, the HPV positivity is significantly higher in CINI, CIN II/III, and SCC (38.60%, 74.60%, 87.50% and 89.05%, P < 0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…HPV16 and HPV18 together accounted for more than 70% of cervical cancer cases 7. This finding agrees with the previous data reported that HPV16 was associated with 60.3% and 85.2% of CIN2+ and invasive cervical cancers, respectively, in Northwest China 8. Oncogenic HPV16/18 infection plays a dominant role in high-grade cervical lesions progression in women, especially in HIV+ individuals.…”
Section: Discussionsupporting
confidence: 90%
“…HPV16 and HPV18 together accounted for more than 70% of cervical cancer cases 7. This finding agrees with the previous data reported that HPV16 was associated with 60.3% and 85.2% of CIN2+ and invasive cervical cancers, respectively, in Northwest China 8. Oncogenic HPV16/18 infection plays a dominant role in high-grade cervical lesions progression in women, especially in HIV+ individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The HPV genotyping of all the samples was detected by Human Papillomavirus Genotyping kit and the results have been reported 12. All 346 specimens fell into one of four groups: cervicitis group (n=57.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study had shown that HPV16, 18 and 58 play a key role in the development of cervical intraepithelial neoplasia (CIN) and invasive squamous cell carcinoma (SCC) in Longnan women. However, the reason for the high incidence of CC and the high mortality is still not clear 12…”
Section: Introductionmentioning
confidence: 99%
“…The success of HPV testing in clinical practice is largely dependent on its high sensitivity and negative predictive value. A previous study showed that the PCR-RDB HPV test is a reliable, sensitive, and accurate method for cervical cancer screening (8,20). In addition, to avoid false-negative results, an internal quality control was used with the PCR-RDB method to evaluate the occurrence of false negatives.…”
Section: Discussionmentioning
confidence: 99%